An efficient and effective image retrieval system on the basis of feature, matching measure and sub-space selection - Mosbah, Mawloud (Array, 2018)
Since its appearance as a research field, Content-based Image Retrieval (CBIR) system has increasingly received an important attention. Review of literature reveals that the efforts put, up to now, in the field address either effectiveness or efficiency. In this paper, we address both accuracy and efficiencythrough introducing an efficient and an effective image retrieval approach based on feature, matching measure and sub-spaceselection. The selection relies on relevance feedback information injected by the user. The approach is tested on Corel-1Kimages database. The obtained results are very promising.